The Fas/CD95 Receptor Regulates the Death of Autoreactive B Cells and the Selection of Antigen-Specific B Cells - HUEBER, Anne-Odile; KONCZ, Gabor (Frontiers in Immunology, 2012)
Cell death receptors have crucial roles in the regulation of immune responses. Here we review recent in vivo data confirming that the Fas death receptor (TNFSR6) on B cells is important for the regulation of autoimmunity since the impairment of only Fas function on B cells results in uncontrolled autoantibody production and autoimmunity. Fas plays a role in the elimination of the non-specific and auto-reactive B cells in germinal center, while during the selection of antigen specific B cells different escape signals ensure the resistance to Fas-mediated apoptosis. Antigen specific survival such as BCR or MHCII signal or coreceptors (CD19) cooperating with BCR inhibits the formation of death inducing signaling complex. Antigen-specific survival can be reinforced by antigen-independent signals of IL4 or CD40 overproducing the anti-apoptotic members of the Bcl-2 family proteins.